Ambulatory glucose profile in managing hypoglycemia in patients with type 2 diabetes mellitus: a case report - Makkar, B. M. (International Journal of Advances in Medicine, 2020)
Continuous glucose monitoring (CGM) was done in a 41 years-old female patient with type 2 diabetes mellitus (T2DM) to evaluate the glucose fluctuations, to achieve better glycemic control. The patient presented to the clinic with lethargy, on/off episodes of extreme weakness, sweating, and tingling sensation in the feet (B/L), with leg pains for the past 3 months. She did not have any history of hypertension and cardiovascular disease. On examination, her blood pressure was found to be 120/70 mm Hg. The fasting plasma glucose was 96 mg/dL, postprandial glucose was 160 mg/dL, and glycosylated hemoglobin was 6.8%. The patient was on metformin (500mg)- glimepiride (2mg) combination, once daily, before breakfast, and metformin (500mg) after dinner. Since the symptoms were related to glucose fluctuations and hypoglycemia, the patient was consequently recommended professional CGM to analyze the complete glycemic profile. The profile obtained from Ambulatory Glucose Profile (AGP) revealed glucose fluctuations observed as hypoglycaemia and hyperglycemic episodes. Consequently, the patient’s treatment regimen was changed. The use of glimepiride was discontinued, and the patient was recommended with vildagliptin (50 mg) and metformin combination (1000 mg) bid with meals. This case study indicates that the use of CGM may help in improving our understanding of glycemic patterns and may have a beneficial effect on glycemic control.